2005
DOI: 10.1002/joc.1196
|View full text |Cite
|
Sign up to set email alerts
|

The latitude of the subtropical ridge over Eastern Australia: The L index revisited

Abstract: Recent research has suggested that the position of the subtropical ridge in mean sea-level pressure over eastern Australia, referred to as the L index, has undergone a substantial poleward shift over the past century. These findings are not supported by calculations of the L index based on daily National Centers for Environmental Prediction reanalysis from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
145
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(156 citation statements)
references
References 16 publications
7
145
4
Order By: Relevance
“…Therefore, these results support previous work (e.g. Drosdowsky, 2005;Timbal et al, 2007;Larsen and Nicholls, 2009;Williams and Stone, 2009) suggesting that the "post-1993 autumn rainfall decline" can be attributed to a strengthening and southward movement of the STR during autumn and a reduction in the frequency of rain producing troughs.…”
Section: What Is Causing the Decrease In Autumn Rainfall?supporting
confidence: 91%
“…Therefore, these results support previous work (e.g. Drosdowsky, 2005;Timbal et al, 2007;Larsen and Nicholls, 2009;Williams and Stone, 2009) suggesting that the "post-1993 autumn rainfall decline" can be attributed to a strengthening and southward movement of the STR during autumn and a reduction in the frequency of rain producing troughs.…”
Section: What Is Causing the Decrease In Autumn Rainfall?supporting
confidence: 91%
“…Thus the SRW propagation associated with this waveguide increased during stronger El Niño events, which occurred in the period 1948-2000. There is a subtropical ridge in mean sea-level pressure over eastern Australia. During El Niño (La Niña) events the ridge is stronger (weaker) and located further equatorward (poleward) than normal (Drosdowsky, 2005). Because of this, El Niño events are often associated with below-normal rainfall and drought over much of northern and eastern Australia.…”
Section: Stationary Wavenumbermentioning
confidence: 99%
“…The STR provides a measure of the high pressure systems that typically lie to the north of the storm tracks and therefore have a role in steering the storm track and the fronts embedded in the westerly flow. The intensity, position and other characteristics of the STR are linked to the frequency and strength of storms and fronts that cross southern Australia, and the STR is therefore an important feature of Australian rainfall variability and change (Pittock 1971;Pittock 1973;Drosdowsky 2005;Larsen and Nicholls 2009;Williams and Stone 2009;Timbal et al 2010;Timbal and Drosdowsky 2013;Whan et al 2013). Both the STR-I and STR-P are negatively correlated with rainfall anomalies in southern Australia on an inter-annual timeframe (Figures 1b and 1c).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have detected a poleward shift in the annual STR-P during periods within the record since 1890 (Kidson 1925;Deacon 1953;Das 1956;Pittock 1971;Pittock 1973), including some showing a significant trend (Das 1956;Thresher 2003). However, Drosdowsky (2005) has critiqued some of the methods used in these studies and found no discernible trend. In terms of intensity, there is more clear-cut evidence that the mean STR-I has intensified in recent decades (Timbal and Drosdowsky 2013).…”
Section: Introductionmentioning
confidence: 99%